2017
DOI: 10.1074/jbc.m117.802272
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric rabbit/human Fab antibodies against the hepatitis Be-antigen and their potential applications in assays, characterization, and therapy

Abstract: Hepatitis B virus (HBV) infection afflicts millions worldwide, causing cirrhosis and liver cancer. HBV e-antigen (HBeAg), a clinical marker for disease severity, is a soluble variant of the viral capsid protein. HBeAg is not required for viral replication but is implicated in establishing immune tolerance and chronic infection. The structure of recombinant e-antigen (rHBeAg) was recently determined, yet to date, the exact nature and quantitation of HBeAg still remain uncertain. Here, to further characterize HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 57 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…Previously, we identified several diverse chimeric rabbit/human Fabs against rHBeAg d using a phage display library (Zhuang et al, 2017). Sequence alignment of the complementarity determining regions (CDRs) of the 24 Fabs revealed two clusters (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we identified several diverse chimeric rabbit/human Fabs against rHBeAg d using a phage display library (Zhuang et al, 2017). Sequence alignment of the complementarity determining regions (CDRs) of the 24 Fabs revealed two clusters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These structures have shown that under oxidizing conditions the cysteine residue at position −7 forms an intramolecular disulfide bond with C61 locking rHBeAg dimers (rHBeAg d ) into an arrangement distinct from that of rHBcAg dimers (rHBcAg d ) (DiMattia et al, 2013). Analysis of HBeAg, isolated from HBV-positive patient plasma samples, by SDS-PAGE under reducing and non-reducing conditions, has confirmed the presence of the disulfide bond between C(−7) and C61 in HBeAg (Zhuang et al, 2017).…”
Section: Introductionmentioning
confidence: 89%
“…The dimeric HBeAg constructs with varying C‐terminal extensions were all expressed in E. coli as previously described . All constructs contained the C48A and C107A mutations (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies with cell cultures have shown that C‐terminal processing occurs in the Golgi by furin generating an e antigen with a C‐terminal sequence extending to R154 and may involve more than one cleavage cycle . This is in contrast to HBeAg isolated from patient sera by affinity chromatography where the C terminus was identified as R151 .…”
mentioning
confidence: 97%
“…In this issue of Structure, Wingfield and colleagues (Eren et al, 2018) present a new approach to fight CHB: targeting HBeAg and dimeric HBcAg. They present three crystal structures of HBeAg and HBcAg dimers in complex with a Fab fragment or an scFV that binds with sub-nanomolar affinity (Zhuang et al, 2017). The HBeAg and HBcAg monomers are very similar: an all-helix protein where long helices 3 and 4 form the intradimer interface and helix 5, along with its following loop and extended structure, has the potential to form the interdimer contacts that support capsid assembly ( Figure 1A).…”
mentioning
confidence: 99%